Hypoxia favors the generation of human plasma cells. Issue 11 (3rd June 2017) - Schoenhals, Matthieu; Jourdan, Michel; Bruyer, Angélique; Kassambara, Alboukadel; Klein, Bernard; Moreaux, Jérôme
ABSTRACT: Plasma cells (PCs) generation occurs in hypoxic conditions in vivo, whereas the relevance of O2 pressure in PC differentiation remains unknown. Using our in vitro PC differentiation model, we investigated the role of hypoxia in PC generation. Hypoxia increases the generation of plasmablasts (PBs) starting from memory B cells, by increasing cell cycle and division number. Reactome analysis demonstrated a significant enrichment of genes involved in HIF1α and HIF2α transcription factor network, metabolism and MYC related pathways in hypoxic compared with normoxic PBs. Hypoxia-induced metabolism alteration and MYC pathway are involved in malignant PC pathophysiology. Therefore, the expression of 28 out of the 74 genes overexpressed in hypoxic PBs compared with normoxic ones was found to be associated with an adverse prognosis (event free survival and overall survival) in newly diagnosed multiple myeloma patients. According to the role of hypoxia in supporting PBs generation through cell cycle induction, c-MYC activation and metabolism alteration, it could be involved in plasma cell tumorigenesis.